Fully Prime Semimodule, Fully Essential Semimodule and Semi-Complement Subsemimodules - Alboshindi, Zaidoon W.; Alhossaini, Asaad A.M. (Iraqi Journal of Science, 2022)
The concept of semi-essential semimodule has been studied by many researchers.     In this paper, we will develop these results by setting appropriate conditions, and defining new properties, relating to our concept, for example (fully prime semimodule, fully essential semimodule and semi-complement subsemimodule) such that: if for each subsemimodule of -semimodule  is prime, then  is fully prime. If every semi-essential subsemimodule of -semimodule  is essential then  is fully essential. Finally, a prime subsemimodule  of  is called semi-relative intersection complement (briefly, semi-complement) of subsemimodule  in , if , and whenever  with  is a prime subsemimodule in , , then .  Furthermore, some results about the above concepts have been mentioned.